Pencegahan Food Loss dan Peningkatan Nilai Ekonomis Pangan Berbasis Potensi Daerah Boyolali: Fruit Leather Pepaya - Diamonda, Sadewa Aziz; Taufik, Moh; Purnasari, Nurwulan; Rusdan, Ilzamha Hadijah (LPkM Universitas Bakrie, 2025)
Boyolali Regency emerged as the leading producer of papayas in Central Java Province in 2023, with a production volume reaching 324,978.72 quintals per year. However, during peak harvest seasons, a significant portion of the harvested papayas fails to be sold optimally due to non-compliance with syarat mutu standards set by middlemen and buyers. The development of fruit leather is proposed as a strategy to mitigate food loss and enhance the economic value of papayas during peak harvest periods, leveraging the region's potential. The stages of implementation are pre-training and post-training. Prior to the implementation of fruit leather production training, 89.47% of members of the Ngudi Santosa Farmers Group in Boyolali Regency were aware of the nutritional content of papayas, yet 63.16% had never processed papayas into food or beverages to increase their utility and economic value. Following the training, over 89% of participants gained an understanding of the fruit leather production process, recognizing that it can be made not only from papayas but also from various other fruits. Additionally, they acknowledged that fruit leather is a functional food product designed to enhance the utility and economic value of fruits. The papaya fruit leather production training received a